Application of the Exoneration Clause in Consumer Protection Judging from Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection - Ataupah, Melaty Belantika; Usman, Siti Ramlah; Jacob, Yossie M.Y. (Universitas Wiralodra, 2023)
This research examines the exoneration clause's application in consumer protection in Bena Village, South Amanuban District, South Central Timor Regency. The data collection methods were interviews and literature study, with data processing and analysis carried out descriptively and qualitatively. The research results show that the application of the exoneration clause occurs in mixed-type food stalls and kiosks, while it does not apply to service businesses. Factors that influence the implementation of exoneration clauses include a lack of education from the government regarding these clauses and a lack of independent consumer literacy. In conclusion, implementing the exoneration clause in consumer protection in Bena Village is not optimal, and it is recommended that there be outreach to consumers and business actors to increase awareness of consumer rights and replace unsuitable products with better ones.